PREDICTIONS OF IMPINGING FLOWS WITHLOW-REYNOLDS NUMBER TURBULENCE MODELS (Sciences & Technologie. B, Sciences de l'ingénieur, 2004)
Several low-Reynolds number k-e  turbulence models have been used to simulate the flow and heat transfer in slot confined and circular unconfined impinging jet configurations. Predictions for the velocity with its fluctuation and Nusselt number are compared to available experimental data. The relative performance of the models is assessed. It has been found that results obtained for the velocity parallel to the plate are in agreement with experimental data but none of models are entirely successful in predicting the radial Reynolds normal stress. For heat transfer, an additional source term in the equation of e was necessary for reducing near-wall length scales and improving the near-transfer predictions by means of the low-Reynolds number k-e turbulence models.